High prevalence of Toxoplasma gondii infection in free-roaming dogs from Ecuador: a proxy for sentinel surveillance of zoonotic threats in low- and middle-income countries - Paredes-Núñez, Darwin; Barragán-Peña, Andrés Esteban; Rodríguez-Pazmiño, Ángel Sebastián; Velez, Alberto; Cruz, Marylin; Salas-Rueda, Mauricio Xavier; Narváez, Alexandra; Orlando, Solón Alberto; Garcia-Bereguiain, Miguel Angel (Frontiers in Veterinary Science, 2025)
Toxoplasmosis is a globally distributed zoonotic disease caused by the protozoan parasite Toxoplasma gondii. Although dogs are not definitive hosts, they can act as environmental sentinels for the risk of toxoplasmosis in humans. In this study, we estimated the seropositivity of T. gondii in stray dogs from Ecuador for the first time and assessed differences in prevalence across regions and between urban and rural settings. A total of 272 free-roaming dogs from the four main regions of Ecuador (Andean, Coastal, Amazon, and Insular regions) were included in this study. Serum samples were collected and tested using a commercial indirect ELISA kit for the detection of T. gondii antibodies. An overall high seropositivity of 39.7% (95% CI: 33.9–45.5%) was observed, with no significant differences between regions or urban and rural zones. This is the first large-scale serological survey of T. gondii in Ecuadorian dogs, confirming widespread environmental exposure to the parasite in the country. Given the large population of free-roaming dogs and the high seropositivity of T. gondii, integrated One Health strategies are needed, including improved stray animal management, public education on responsible pet ownership, and environmental control measures to mitigate the risk of toxoplasmosis and related diseases in Ecuador.